Diversity in the composition of pleural cavity and oral cavity microbiota in different bacterial empyema - Huang, Yun; Gao, Qing-Hua; Liu, Chen-Jian; Su, Ting; Liu, Jie; Liang, Zheng-Yi; Zhao, Zheng-Ju; Chen, Li-Ping; Yi, Yong-Ning; Li, Xiao-Ran; He, Jian (Frontiers in Microbiology, 2025)
IntroductionRecent studies have proposed primary empyema and demonstrated a correlation between it and the microbial composition of the oral cavity. However, no study has systematically characterized the differences in microbial composition between primary and secondary empyema. Furthermore, the correlation between the characteristics of empyema and oral microbiota remains to be explored.MethodsThe study included forty-six patients diagnosed with empyema. Hydrothorax was collected from all patients, and mouthwash samples were collected from 24 patients. Both types of samples underwent amplification and sequencing using primer sets specific for the 16S rRNA gene.Results and discussionCompared with the primary empyema group, the pleural cavity microbial diversity of pneumonia complicated with empyema was significantly decreased (p < 0.05). At the phylum level, the relative abundance of Proteobacteria was significantly higher in the primary empyema group than pneumonia with empyema (p < 0.05). At the genus level, the abundance of Streptococcus, Escherichia-Shigella, and Corynebacterium increased in the primary empyema group, while the abundance of Campylobacter, Salmonella, Bacillus, and Staphylococcus decreased (p > 0.05). The shared sequences between the hydrothorax samples and mouthwash samples from the patients with empyema contributed to 94% of the total sequences used in these analyses. Correlation analysis indicated that the presence of Streptococcus constellatus in empyema is positively correlated with leukocytes and neutrophils, and negatively correlated with lymphocytes (p < 0.05).